Ilmu Dalam Pandangan Normatif Islam: Telaah Epistemologis Atas Ayat-Ayat Al-Qur'an dan Hadis - Kiki Wiyandi; Sri Pujiati; Ris’an Rusli; Romli (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
This article examines the concept of knowledge ('ilm) in the normative Islamic perspective through an epistemological approach, based on the verses of the Qur'an and the hadiths of the Prophet Muhammad (PBUH). Unlike Western epistemology, which strictly separates reason, empiricism, and intuition, Islam offers an integration of all three within the framework of tawhid (divine unity). This research employs the methods of thematic exegesis (tafsir maudhu'i) and thematic hadith extraction (takhrij). The main findings indicate that: (1) the sources of knowledge in Islam are not limited to the sensory world (hissi) and reason ('aql), but also include the purified heart (qalb) as a receiver of ladunni knowledge (divinely gifted knowledge) as well as revelation as the highest source; (2) the validity of knowledge is measured not only by logical coherence and empirical verification, but also by its alignment with revelation and its moral impact (akhlak); (3) the ultimate purpose of knowledge is al-'ilm al-nafi' (beneficial knowledge) that brings one closer to Allah and benefits the universe. In conclusion, normative Islamic epistemology offers a holistic paradigm of knowledge that simultaneously integrates ontological, epistemological, and axiological aspects, while also serving as a solution to the dichotomy of knowledge that has long characterized Islamic education.